벼줄무늬잎마름병의 발생변화 - 이봉춘(Bong Choon Lee); 조상윤(Sang-Yun Cho); 윤영남(Young-Nam Yoon); 강인정(In Jeong Kang); 이종희(Jong Hee Lee); 곽도연(Do Yeon Kwak); 신동범(Dong Bum Shin); 강항원(Hang-Won Kang) (Sigmulbyeong yeon'gu, 2012)
We surveyed the occurrence of Rice stripe virus (RSV) disease in 672 fields from 29 rice representative area in July 2012 as nationwide survey for RSV occurrence since 2008. We confirmed occurrence of virus disease in 18 areas, in west coast region including Secheon, Taean, Buwan and Cheorwon. RSV incidence rates of plant in Sacheon and Buan were less than 0.01% and 0.15%, respectively, showing similar rate with the nationwide survey carried out in 2008, whereas incidence rate of field declined from 19.9% in 2008 to 4.9% in 2012. Earlier, RSV occurred largely across the southern region of Korea. In 2001, RSV disease was found in Gangwha and Gyeonggi-do, the northern region of Korea. In 2007, RSV appeared in west coast; Buan in Jeollabuk-do and Seocheon in Choongnam-do. After migration of the vector, small brown plant hopper, from China in 2009, RSV is becoming a pandemic. 본 조사는 2008년 이후 4년만에 실시한 RSV 전국조사 결과로서 2012년 벼 재배대표지역 29개 지역 672필지를 대상으로 RSV의 발생을 조사하였다. RSV의 발생은 서해안지역인 서천, 태안, 부안 및 철원 등 18개 지역에서 확인되었다. 발병주율은 서천 0.01% 이하에서 부안 0.15%, 이병필지율은 4.9%로 조사되었다. 이것은 2008년의 전국조사와 비슷한 경향이었으나 이병필지율은 2008년의 19.9%에서 2012년의 4.9%로 감소하였다. 지금까지 벼줄무늬잎 마름병은 남부지방에 국한되어 발생되어 왔으나 2001년에 경기, 강화지역까지 북상하였으며, 2007년에는 서해안지역인 전북 부안, 충남 서천 지역에 대발생하였다. 현재는 2009년 중국으로부터 애멸구 비래가 확인된 이후 서해안 지역이 발생상습지화 되고 있으며 전국적으로 만연하는 병이 되고 있다.